Study of the association between diabetes mellitus type2 and intraocular pressure and its relation with central corneal thickness - رجب محمود; اسكندر صبا (Latakia University Journal -Medical Sciences Series, 2021)
Aim: To study the values ​​of intraocular pressure (IOP) in diabetics compared to healthy subjects, and to study the values ​​of central corneal thickness(CCT) as a primary mediating factor affecting the intraocular pressure. As well as studying the relationship between intraocular pressure and age, duration of diabetes, and blood sugar value.Also, lens thickness, anterior-posterior axial length of the eye ball, anterior chamber depth, spherical equivalent value, corneal endothelial cell count, and the presence of non-proliferative diabetic retinopathy as secondary mediators of the relationship between diabetes and intraocular pressure. materials and methods: 114 patients (228 eyes) participated in the study, distributed between 57 type 2 diabetes patients (case) and 57 control patients, whose ages ranged between (42-78) years. Intraocular pressure was measured for all cases and controls by Goldman applanation tonometry. In addition, a number of variables that may affect the intraocular pressure (such as central corneal thickness, anterior chamber depth, axial eye length, spherical equivalent, corrected visual acuity, endothelial cell count, and the presence of nonproliferative diabetic retinopathy) using a specular microscope, Echo A, slit lamp, autorefractometer. Results: A statistically significant increase was observed in the intraocular pressure values ​​of type 2 diabetics compared to healthy subjects, as the average values ​​of intraocular pressure in the diabetic group were 16.6 ± 4,4 mmHg compared with the healthy subjects 12.8 ± 3.2 mmHg. Iop was higher in the non-proliferative retinopathy group NPDR than in the other group without retinopathy of the retina with values ​​of intraocular pressure respectively: 19.05 ± 3.8 mmHg, 14.16 ± 3.5 mmHg. An increase in central corneal thickness, lens thickness, and spherical equivalent, and decreased endothelial cell count, anterior chamber depth, anterior posterior axial length, and corrected visual acuity were observed in the diabetic group. There was a positive correlation between intraocular pressure and central corneal thickness. There was a positive correlation between IOP and each of: age, duration of diabetes, blood sugar value, presence of non-proliferative diabetic retinopathy, lens thickness, and spherical equivalent. Whereas, the relationship was inverse between intraocular pressure and each of the corrected visual acuity and endothelial cell count. We did not observe a statistically significant relationship between IOP and anterior posterior axial length of the eye. Conclusion: The intraocular pressure is higher in the glycemic than in the controls. The thickness of the central cornea plays the main role in this elevation. Likewise, the increased thickness of the lens, the increase in the spherical equivalent, the decrease in the anterior chamber depth, the decrease in the corrected visual ability, the presence of non-proliferative diabetic retinopathy and the decrease of corneal endothelial cell count plays a role in the increased intraocular pressure in diabetes.